Social Inclusion And Democracy In The Emblematic Educational Institutions Of District 09D05-Ecuador: Management Competency Model 2023 - Aguas Villon, Laura Elizabeth (2024)
The objective of the research is to know the relationship between the variable's social inclusion and democracy in educational institutions. The approach is quantitative, the type of research is pure, non-experimental, cross-sectional. The population is made up of 286 teachers from iconic institutions of an educational district and the sample was 165 institutes. The technique that was used is the questionnaire; to measure social inclusion and democracy; A pilot study was carried out, the results of which were acceptable. Additionally, expert validation was applied for the validity of the instrument. It was concluded that educational social inclusion is mostly rated at an "advanced" level; by 85.5%; followed by the "average" rating by 13.3% and "low" by 1.2%. The results of democracy show that 64.2% are qualified in the "advanced" range; 21.8% in the "medium" range and 13.9% in the "low" range. The data obtained have a normal distribution. The linear regression between Social Inclusion and educational Democracy; returns 0.215 points; being a very low value; which implies that there is no possible correlation; thus, it is ratified by the "R squared"; whose value is 4.6%; Spearman's rho reaches a value of 0.286; therefore, there is a very low correlation and it is not significant.